(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In this article, the difference between acute and chronic course of sheep paramphistomatosis, clinical signs of the disease in relation to pathogenesis and the effect of parasite migration is written. The results of the data obtained on the basis of clinical examinations of infected sheep in farms are presented.